REPERCUSSIONS OF CORE STRENGTH TRAINING ON SOCCER PLAYERS’ PERFORMANCE - Xing,Yan’an (2023)
ABSTRACT Introduction: Soccer players are athletes who need to develop advanced characteristics of strength and speed. The resistance training of the muscles involved in the core is a new training theory applicable to modern sports that is gaining prominence due to its amazing results. It is of great value for researchers to integrate the strengths of core strengthening into soccer training, improve their protocols, and compensate for their limitations. Objective: This study aimed to analyze the relationship between core strength training and physical conditioning in soccer players. At the same time, this article discusses the influence of core muscle strength characteristics on athletes’ physical performance. Methods: This article selects advanced soccer players as research subjects. Volunteers were randomly divided into two groups (control and experimental groups). The experimental group received core muscle strength training, while the control group received daily training. This paper analyzed the muscle strength characteristics of the two groups of volunteers. Then, this paper conducts a statistical and mathematical analysis of the muscle strength level data in two groups of athletes. Results: The experimental group showed significant differences in bilateral hip and ankle joint flexors after core muscle strength training (P<0.01). The relative peak moment of flexion and extension of the left hip was lower than that of the right hip, a factor justified by the predominant motor laterality principle on the players. The muscle strength of the left knee and ankle joints was greater than that of the right. Both experimental and control groups showed that the strength of the ankle flexors was better than the ankle extensors (knee toe flexors). The data were very significantly different (P<0.01). Conclusion: Muscular endurance training can help improve the physical conditioning of soccer players. Athletes can reinforce core strength training in their daily training. Level of evidence II; Therapeutic studies - investigation of treatment outcomes.